Injection molded self‐hybrid composites based on polypropylene and natural fibers. Issue 9 (29th December 2013) - Pérez‐Fonseca, A.A.; Robledo‐Ortíz, J.R.; Moscoso‐Sánchez, F.J.; Rodrigue, D.; González‐Núñez, R.
<x xml:space="preserve">Abstract</x> Self‐hybrid thermoplastic composites (combination of two fiber sizes) were obtained by injection molding using pine or agave fibers with polypropylene (PP). The effect of self‐hybridization was determined through mechanical properties and water absorption for different total fiber contents between 10 and 30% wt. The results showed that impact strength (30% of fiber) and tensile modulus (20% of fiber) were improved by self‐hybridization compared with composites formulated with only one fiber size. Flexural properties were not improved by self‐hybridization. On the other hand, the combination of two fiber sizes had no effect on the water absorption behavior of these composites. Overall, the total fiber content was found to be an important parameter with 20% being the optimum condition where self‐hybridization provides the best mechanical properties. POLYM. COMPOS., 35:1798–1806, 2014. © 2013 Society of Plastics Engineers